(untitled) (Third Sector Social Economic Review, 2016)
In this study, it is aimed to determine the satisfaction levels of customers who benefited from bancassurance in İstanbul Avcılar District. Additionally, in this study, if the mentioned customer’s feedbacks differ according to some variables are also examined by ANOVA. Results of there search shows that, participant sprefer bank insurance activities because it provides convenience in credit transactions; they find bancassurance safe but find insurance agents’ insurance activities more secure than banks’ insurance activities. In addition, it is observed that, customer feedbacks differ in terms of some variables while they do not differ in terms of other variables.